Employing modern technology to support the teaching and learning process in primary schools in Al-Dakhiliyah Governorate in the Sultanate of Oman - Al-Durai, Ali Saif (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the extent to which modern technology is employed to support the teaching and learning process, as well as the challenges of using modern technologies in basic education schools in the Sultanate of Oman. The study adopted an experimental methodology and utilized multiple tools, including observation, interviews, and learning tours. These tools were applied to a sample of six female teachers. The study's findings regarding the employment of modern technology revealed that it can be effectively integrated into the teaching and learning process in schools by developing a clear strategy for its implementation. The results showed a significant increase in the use of smart boards from 52% to 100%, educational games from 27% to 72%, and social media platforms in the educational process from 22% to 85%. The appropriate use of interactive whiteboards in the educational process rose from 20% to 90%. The use of educational applications increased from 7% to 54%, while the use of educational blogs grew from only 10% to 65%. The results also demonstrated improvements in teachers' knowledge and skills after the implementation of the professional development program. Additionally, the number of applications used in the classroom to support teaching and learning increased from two before the procedural (professional development) program to seven applications. Based on the findings, the researcher recommended enhancing professional development in schools in the field of modern technology and fostering teachers’ self-learning skills to ensure the continuous improvement of their knowledge and skills in educational technology. The researcher also suggested conducting further similar studies on a larger sample.
Keywords: Ad-Dakhiliyah Governorate; Modern technology; primary schools; teaching and learning process